Isolation and Characterization in a Soil Conditioned With Foaming Agents of a Bacterial Consortium Able to Degrade Sodium Lauryl Ether Sulfate - Rolando, Ludovica; Grenni, Paola; Rauseo, Jasmin; Pescatore, Tanita; Patrolecco, Luisa; Garbini, Gian Luigi; Visca, Andrea; Barra Caracciolo, Anna (Frontiers in Microbiology, 2020)
The anionic surfactant Sodium Lauryl Ether Sulphate (SLES) is the principal component of several commercial foaming products for soil conditioning in the tunneling industry. Huge amounts of spoil material are produced during the excavation process and the presence of SLES can affect its re-use as a by-product. Anionic surfactants can be a risk for ecosystems if occurring in the environment at toxic concentrations. SLES biodegradability is a key issue if the excavated soil is to be reused. The aim of this study was to identify bacteria able to degrade SLES, so that it could potentially be used in bioaugmentation techniques. Enrichment cultures were performed using bacterial populations from spoil material collected in a tunnel construction site as the inoculum. A bacterial consortium able to grow in a few hours with SLES concentrations from 125 mg/L to 2 g/L was selected and then identified by Next Generation Sequencing analysis. Most of bacteria identified belonged to Gamma-Proteobacteria (99%) and Pseudomonas (ca 90%) was the predominant genus. The bacterial consortium was able to degrade 94% of an initial SLES concentration of 250 mg/L in 9 hrs. A predictive functional analysis using the PICRUSt2 software showed the presence of esterase enzymes, responsible for SLES degradation. The bacterial consortium selected could be useful for its possible seeding (bioaugmentation) on spoil material from tunneling excavation.